Merging Passivation in Synthesis Enabling the Lowest Open‐Circuit Voltage Loss for PbS Quantum Dot Solar Cells. Issue 5 (20th December 2022) - Liu, Yang; Wu, Hao; Shi, Guozheng; Li, Yusheng; Gao, Yiyuan; Fang, Shiwen; Tang, Haodong; Chen, Wei; Ma, Tianshu; Khan, Irfan; Wang, Kai; Wang, Changlei; et al.
Abstract: The high open‐circuit voltage ( V oc ) loss arising from insufficient surface passivation is the main factor that limits the efficiency of current lead sulfide colloidal quantum dots (PbS CQDs) solar cell. Here, synergistic passivation is performed in the direct synthesis of conductive PbS CQD inks by introducing multifunctional ligands to well coordinate the complicated CQDs surface with the thermodynamically optimal configuration. The improved passivation effect is intactly delivered to the final photovoltaic device, leading to an order lower surface trap density and beneficial doping behavior compared to the control sample. The obtained CQD inks show the highest photoluminescence quantum yield (PLQY) of 24% for all photovoltaic PbS CQD inks, which is more than twice the reported average PLQY value of ≈10%. As a result, a high V oc of 0.71 V and power conversion efficiency (PCE) of 13.3% is achieved, which results in the lowest V oc loss (0.35 eV) for the reported PbS CQD solar cells with PCE >10%, comparable to that of perovskite solar cells. This work provides valuable insights into the future CQDs passivation strategies and also demonstrates the great potential for the direct‐synthesis protocol of PbS CQDs. Abstract : Synergistic passivation is performed in the direct synthesis of conductive lead sulfide colloidal quantum dot (PbS CQD) inks. The improved passivation effect is intactly delivered to the final photovoltaic device, leading a high open‐circuit voltage ( V oc) ) of 0.71 V and efficiency of 13.3%, which results in the lowest V oc loss (0.35 eV) for the reported PbS CQD solar cells.